A Hello Vaccines: Development of An Android Mobile Game Application on Covid-19 Vaccination Awareness - Zheng Yan, Khor; Senan, Norhalina (Applied Information Technology And Computer Science, 2022)
COVID-19 pandemic has been happening around the world since 2019. Malaysia’s government has conditionally approved five COVID-19 vaccines and started to urge and encourage teenagers to receive the vaccination due to the preparation of the school reopen policy. Unfortunately, much fake news and inappropriate remarks on social media could have influenced people’s faith and confidence in COVID-19 vaccinations, particularly among adolescents. Currently, many methods have been implemented for delivering the awareness related to COVID-19 vaccinations such as via social media, television news, and advertisements. However, these methods are still possessing some limitations, especially in terms of the fun gaming approach. Therefore, Hello Vaccines as an android mobile game application is developed to enhance understanding and awareness about COVID-19 Vaccination among teenagers through a fun gaming approach. Game Development Life Cycles is utilized to design and implement Hello Vaccines. Unity Game Engine, Visual Studio, and Adobe Illustrator 2020 are utilized throughout the development of this application. The overall result of the user acceptance test on the Hello Vaccines mobile game application has positive feedback with a favorable result of 89.3%. It indicates that the application reached a higher user acceptance level.